Analysis of External Water Pressure for a Tunnel in Fractured Rocks. (30th January 2017) - Liu, Ze-jun; Huang, Yong; Zhou, Ding; Ge, Hong
Abstract : External water pressure around tunnels is a main influential factor in relation to the seepage safety of underground chambers and powerhouses which make managing external water pressure crucial to water conservation and hydropower projects. The equivalent continuous medium model and the discrete fracture network (DFN) model were, respectively, applied to calculate the seepage field of the study domain. Calculations were based on the integrity and permeability of rocks, the extent of fracture development, and the combination of geological and hydrogeological conditions in the Huizhou pump-storage hydropower station. The station generates electricity from the upper reservoir and stores power by pumping water from the lower to the upper reservoir. In this paper, the external water pressure around the cavern and variations in pressure with only one operational and one venting powerhouse were analyzed to build a predictive model. The results showed that the external water pressure was small with the current anti-seepage and drainage system that normal operation of the reservoir can be guaranteed. The results of external water pressure around the tunnels provided sound scientific evidence for the future design of antiseepage systems.